Fintech literacy and digital entrepreneurial intention: Mediator and Moderator Effect - Thuy Thu Nguyen; Trang Thu Dao; Tram Bao Tran; Huong Thi Thu Nguyen; Linh Thi Ngoc Le; Nguyen Thi Thao Pham (International Journal of Information Management Data Insights, 2024)
Our paper contributes to the nascent field of digital entrepreneurship by proposing a model linking students’ Fintech literacy to digital entrepreneurial intention based on the application of the Theory of Planned Behaviour. Structural equation modelling (SEM) with bootstrapping method was used to examine the relationships between variables from a sample of 466 Vietnamese university students. The findings reveal that personal attitude towards digital entrepreneurship and perceived behavioural control are the key determinants of digital entrepreneurial intention. Three Fintech literacy dimensions (namely blockchain, crowdfunding, and AI literacy) are found to directly affect digital entrepreneurial intention. Furthermore, the mediating roles of attitude towards digital entrepreneurship and perceived behavioural control are empirically supported. Family business background can increase the impacts of Fintech literacy on Digital entrepreneurial intention. This study provides empirical evidence in the field of digital entrepreneurship in a developing transition economy. Research suggests recommendations to promote digital entrepreneurship intention among students.